The Influence of Teacher Management on the Quality of Graduates at Batu Belah 006 Public Elementary School, East Siantan District, Anambas Islands Regency - Rizadiliyawati, Rizadiliyawati; Syaifudin, Muhammad; Zaitun, Zaitun (Global Education Journal, 2025)
Education must be able to produce graduates who think globally and act locally, and are grounded in noble morals. The purpose of this study is to analyze the influence of teaching staff management on the quality of graduates at SDN 006 Batu Belah, Siantan Timur District, Anambas Islands Regency. The type of research is quantitative. The results of the study found that the teaching staff management variable has an influence on the quality of graduates at SDN 006 Batu Belah by 42%, this means that teaching staff management can be used as a tool to predict the quality of graduates. The better the teaching staff management, the better the quality of graduates. 2) The results of the study found that the teaching staff management variable has an influence on the quality of graduates at SDN 006 Batu Belah by 42%. This means that there is a significant influence of teaching staff management and the quality of graduates at SDN 006 Batu Belah.